The role of the Balanced Score Card in evaluating the IT department - .u.Talal .ALSHmmari, Nahla; Mahdi Jawad Al-Kawaz, Salah (Iraqi Journal for Administrative Sciences, 2024)
The aim of the research is to demonstrate the role of balanced label card technology (BSC) in evaluating strategic performance in light of the most important changes that occurred in the modern business environment, most notably the intense competition with foreign products in the Iraqi market. The two banks research sample and field coexistence in these two banks and personal interviews with officials and their workers in addition to the questionnaire, the research reached several conclusions, the most important of which is the use of the balanced score card in evaluating the performance of the IT department in the two banks, the research sample will contribute to ensuring the extent of achievement of the two banks For their strategic objectives and the possibility of identifying their weaknesses, and then taking the necessary measures to address and control them., In light of the conclusions, the researchers suggested several recommendations, the most important of which is the need for companies to use the balanced score card to evaluate the performance of information technology management and to ensure the achievement of its strategic objectives to identify weaknesses in its performance and take the necessary measures to address and control them.